Pierre de Charentenay, S.J., The Philippines: An Asiatic and Catholic Archipelago - Tolosa, Benjamin T., Jr. (Archīum Ateneo, 2024)
Pierre de Charentenay, S.J., The Philippines: An Asiatic and Catholic Archipelago